The retransmission of rumor-related tweets: Characteristics of source and message - CHUA, Alton Y. K. (Institutional Knowledge at Singapore Management University, 2016)
This paper investigates the characteristics of rumor-related tweets that would attract retransmission. Drawing on the uses and gratifications (U & G) and influential users' theories, it proposes a rumor retransmission model which comprises variables associated to the source and the message of the tweets. From a total of 5,885 rumor-related tweets about the death of the founding Prime Minister of Singapore Lee Kuan Yew collected, 800 original tweets without a "RT" prefix were selected for analysis. It was found that the experience and connectivity of the source are correlated to retransmission. The age of the account and number of followers have positive relationships with retransmission, while the number of tweets posted and number of friends have negative relationships. For characteristics of the message, attractiveness and expressions of sense of belonging are positively related to retransmission but the use of directed messages and medium-specific features, namely hashtags and URLs have negative relationships with retransmission. Messages with low level of emotions trigger more retweets than those without emotional expressions and those that are highly emotional. Results could suggest that in inauspicious contexts such as the rumored death of a political figure, Twitter users appear to favor less complex content and seem to be discerning and rational in making retransmission decisions.